All Days 2015
DOI: 10.2118/175506-ms
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clay Content and Type on Oil Recovery Under Low Salinity Waterflooding in North Sea Reservoirs

Abstract: A high level screening has been performed of UKCS oil fields to identify the most likely LSWF candidates utilising screening criteria with a focus on kaolinite clay content. The screening results suggest that approximately 57% of the fields have 6 % or higher kaolinite clay content. Of these fields 26 % were water-wet and 74 % were mixed-wet in terms of wettability. This suggests that a significant number of fields would fall within the eligibility for consideration of LSWF EOR although their suitability will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Field tests and core-flooding experiments have verified that LSWF improves the oil recovery process by 5%-38% more than that by traditional water flooding techniques [1][2][3][4]. The usage of brines with low salinity concentration and lower ionic strength plays a significant role in the wettability alteration in both sandstone and carbonate reservoir rocks.…”
Section: Introductionmentioning
confidence: 95%
“…Field tests and core-flooding experiments have verified that LSWF improves the oil recovery process by 5%-38% more than that by traditional water flooding techniques [1][2][3][4]. The usage of brines with low salinity concentration and lower ionic strength plays a significant role in the wettability alteration in both sandstone and carbonate reservoir rocks.…”
Section: Introductionmentioning
confidence: 95%
“…It was also suggested that based on no significant difference in responses to imbibition and waterflood by two sandstone rocks of widely different clay content, different pore geometry and concomitant clay mineral distributions may have impacted the results. Austad et al [52] argued that brine-dependent recovery is more favored by clay minerals with high cation exchange capacity (CEC), which varies in the following ascending order of clay types: kaolinite > chlorite > illite > smectite [52,75,164,169,170]. Several other studies worked on the premise of the necessity of clay minerals for optimum performance of brine-dependent recovery, without identifying the clay minerals type(s) that had a greater impact on flooding performance.…”
Section: Sandstone Rocksmentioning
confidence: 99%
“…It was also suggested that based on no significant difference in responses to imbibition and waterflood by two sandstone rocks of widely different clay content, different pore geometry and concomitant clay mineral distributions may have impacted the results. Austad, et al [102] argued that the brine-dependent recovery is more favoured by clay minerals with high cation exchange capacity (CEC), which varies in the following ascending order by clay types: kaolinite > chlorite > illite > smectite [14,102,103,108,109]. Several other studies worked on the premise of the necessity of clay minerals for optimum performance of brine-dependent recovery, without identifying the clay minerals type(s) that a greater impact on flooding performance.…”
Section: Sandstone Rocksmentioning
confidence: 99%